2002
DOI: 10.1123/jab.18.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Two Methods for Estimating Tendinous Tissue Elongation during Human Movement

Abstract: During dynamic activities it is difficult to assess in vivo length changes in human tendon and aponeurosis. The present study compared the outcome of two methods during unilateral squat jump and drop jump performances of four volunteers. Tendinous tissue elongation of vastus lateralis muscle was estimated using either (a) direct measurement of in vivo fascicle length change and muscletendon length estimation (kinematic method), or (b) prediction using a quadratic force function in combination with direct tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…However, in some cases the tendon is reported to be more compliant than the aponeurosis . While there have been no direct studies of series elasticity in the equine vastus lateralis, there is substantial strain in the elastic elements of the human vastus lateralis Fukunaga et al, 2002;Ichinose et al, 2000;Muraoka et al, 2001) and at least one study (Finni and Komi, 2002) supports the idea that, in muscles in general, the aponeurosis may be more compliant than the tendon (Kawakami and Lieber, 2000). In the absence of data on the compliance of the series elasticity of the equine vastus lateralis, we cannot unambiguously account for the differences in observed and predicted strain.…”
Section: Strain Estimated From Kinematicsmentioning
confidence: 77%
“…However, in some cases the tendon is reported to be more compliant than the aponeurosis . While there have been no direct studies of series elasticity in the equine vastus lateralis, there is substantial strain in the elastic elements of the human vastus lateralis Fukunaga et al, 2002;Ichinose et al, 2000;Muraoka et al, 2001) and at least one study (Finni and Komi, 2002) supports the idea that, in muscles in general, the aponeurosis may be more compliant than the tendon (Kawakami and Lieber, 2000). In the absence of data on the compliance of the series elasticity of the equine vastus lateralis, we cannot unambiguously account for the differences in observed and predicted strain.…”
Section: Strain Estimated From Kinematicsmentioning
confidence: 77%
“…It has been shown previously that the error in estimating VL L f using trigonometric extrapolation was 2-7% (10) and 5.9% (15), which was considerably lower than found in the present study (12.6 Ϯ 8.1%). This discrepancy might be attributable to the present use of EFOV US imaging, with which it was possible to make direct comparisons (we measured the length of the same fascicle using both methods), or to comparisons in other studies being done at different muscle lengths and contraction intensities where aponeurosis and fascicle curvature was different (10,15). Regardless, the present data and those of others have revealed substantial inaccuracies in the estimation method, which in some circumstances may be of a magnitude greater than the longitudinal changes in L f reported previously (5, 28 -31).…”
Section: Discussionmentioning
confidence: 96%
“…One of the limitations in this study is that fascicle length was not measured directly. Due to the time commitments of the athletes and the time‐intensive nature of direct measure, trigonometric estimation of FL was favored in line with the findings of previous research . However, previous research has suggested that a degree of curvature exists in both the fascicle and the aponeuroses of the muscle .…”
Section: Discussionmentioning
confidence: 99%